MACROHISTORIA, MICROHISTORIA O HISTORIA - Sanmartín, J. (Antigüedad y Cristianismo, 1995)
Knowledge of the past is a mental processing of data, and as such it is not different from knowledge of «normal» things. Things (objects) and words are interconnected by concepts (notions); in the historical knowledge things (events) and words (texts) are interconnected by the sense (meaning) in which the knowing subject digest (ananges) the past. This arrangement is a product of the historical competence of the subject, and is here called History. In this paper History is asserted to be a strictly Linguistic discipline.